Synthesis of the 6-Substituted Imidazo[1,2-a]Pyridine-3-yl-2- Phosphonopropionic Acids as Potential Inhibitors of Rab Geranylgeranyl Transferase - Kusy, Damian; Marchwicka, Aleksandra; Małolepsza, Joanna; Justyna, Katarzyna; Gendaszewska-Darmach, Edyta; Błażewska, Katarzyna Magdalena (Frontiers in Chemistry, 2021)
Twelve phosphonopropionates derived from 3-IPEHPC were synthesized and evaluated for their activity as inhibitors of protein geranylgeranylation. The nature of the substituent in the C6 position of imidazo[1,2-a]pyridine ring was responsible for the compound’s activity against Rab geranylgeranyl transferase (RGGT). The most active inhibitors disrupted Rab11A prenylation in the human cervical carcinoma HeLa cell line. The esterification of carboxylic acid in the phosphonopropionate moiety turned the inhibitor into an inactive analog.